Experiences and views of patients, carers and healthcare professionals on using modems in domiciliary non-invasive ventilation (NIV): a qualitative study. Issue 1 (10th March 2020) - Mansell, Stephanie K; Kilbride, Cherry; Wood, Martin J; Gowing, Francesca; Mandal, Swapna
Abstract : Background: Advances in technology means that domiciliary non-invasive ventilation (NIV) devices can be remotely monitored via modems in patients' homes. Possible benefits and challenges of modem technology have yet to be established. This study explored the perspectives and experiences of patients, their carers and healthcare professionals (HCPs) on the addition of modem technology in managing home NIV. Methods: A qualitative study using a combination of focus groups for HCPs and interviews for carers/patients was undertaken. 12 HCPs and 22 patients/carers participated. These focus groups and interviews were audio-recorded, transcribed verbatim and analysed thematically. Results: Five main themes were identified. 'Surveillance: a paradox of findings': HCPs were concerned about unduly scrutinising patients' lives, potentially impacting on HCP patient relationships. Conversely, patients welcomed modem monitoring and did not express concerns regarding invasion of privacy. 'Sanctions': HCPs reported the modem increased access to care and allowed appropriate assessment of ongoing treatment. 'Complacency and ethics': HCPs expressed concerns patients may become complacent in seeking help due to expectations of modem monitoring, as well as being concerned regarding the ethics of modems. There was a suggestion patients and carers' expectations of monitoring were different to that of clinical practice, resulting in complacency in some cases. 'Increased time for patient focused care': HCPs in the focus groups described a number of ways in which using modems was more efficient. 'Confidence: can be improved with technology': patients and carers were positive about the impact of the modems on their health and well-being, particularly their confidence. Conclusion: HCPs expressed concerns about surveillance were not corroborated by patients, suggesting acceptability of remote monitoring. Data suggests a need for increased clarity to patients/carers regarding clinical practice relating to responsiveness to modem data. The issue of complacency requires further consideration. Modem technology was acceptable and considered a useful addition by HCPs, patients and carers. Trial registration number: NCT03905382